Acute splenic sequestration in a pregnant woman with homozygous sickle-cell anemia - Maia, Carolina Bastos; Nomura, Roseli Mieko Yamamoto; Igai, Ana Maria Kondo; Fonseca, Guilherme Hencklain; Gualandro, Sandra Menosi; Zugaib, Marcelo (São Paulo Medical Journal, 2013)
CONTEXT: Homozygous (SS) sickle-cell anemia complicated by acute splenic sequestration in adults is a rare event, and it has never been reported during pregnancy. CASE REPORT: A 25-year-old woman with homozygous (SS) sickle-cell disease was hospitalized at 32 weeks’ of gestation presenting weakness, abdominal pain, fever and hemoglobin of 2.4 g/dl. Abnormal fetal heart rate was detected by means of cardiotocography, and 5 units of packed red cells were transfused. Cesarean was performed at 37 weeks. Both mother and baby were discharged in a good general condition. CONCLUSION: This case report demonstrates the importance of immediate blood transfusion for treatment of fetal distress in cases of splenic sequestration during pregnancy. This treatment is essential for avoiding maternal and fetal complications.